Improving Mathematics Learning Outcomes For Fourth Grade Students At SD Negeri 0309 Pagaranbira Using Unit Square Media - Supiati Supiati (STKIP Rokania Pasir Pangaraian, 2022)
In the context of square unit media on flat shapes, how the application of square unit media in broad flat shapes learning affects student activities and learning outcomes will be discussed. In particular, this study aims to describe student activities and student learning outcomes using the media unit squared on the flat plane of fourth grade students at SD Negeri 0309 Pagaranbira. The method used in this research is qualitative and descriptive research. The data of this study were obtained from students of SD Negeri 0309 Pagaranbira. The subjects of this study were the fourth grade students of SD Negeri 0309 Pagaranbira, totaling 36 students. Collecting data using observation and tests. Researchers observe student learning activities, and tests are questions that researchers give to students. Data processing uses data reduction, data presentation, conclusion drawing/validation, and percentages. The results showed that the application of square unit media to student activities in the fourth category of SD Negeri 0309 Pagaranbira in the field of flat shape learning showed that not all of the 12 aspects observed by the researchers could be implemented by students in the wide flat wake learning process. surface. Fourth graders form. Aspects of the learning process that have not been realized include cutting square units, using the formula for the area of ​​a rectangle. The results of the learning test showed as many as 27 students who completed and as many as 6 students who did not complete. From the results of data analysis, it can be seen that the student integrity test has been completed. Referring to the KKM in the school environment,